Vitamin D role in smoking women and cardiac remodeling - Fidelix, Melaine Priscila [UNESP]; Tanni, Suzana Erico [UNESP]; Roscani, Meliza Goi [UNESP]; Mesquita, Carolina Bonfanti [UNESP]; Schelini, Karime Nafad de Melo [UNESP]; Polegato, Bertha Furlan [UNESP]; Gaiolla, Paula Schmidt Azevedo [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Zornoff, Leonardo Antonio Memede [UNESP]; Papini, Silvia Justina [UNESP]; de Godoy, Irma [UNESP]; de Paiva, Sergio Alberto Rupp [UNESP] (Springer Nature, 2016)
Background: The objective of the study is to evaluate the influence of serum vitamin D concentrations and smoking status in cardiac structure and function. Methods: The participants of this study were healthy women smokers (n = 18, mean age 52.8 years), ex-smokers (n = 18, mean age 51.7 years), and never smokers (n = 19, mean age 44.4 years). All participants underwent assessment of body composition, dietary intake, sun exposure frequency, vitamin D serum determination, and echocardiographic assessment. All data underwent statistical analysis. Results: The three groups were classified as overweight. The group of ex-smokers showed significantly higher vitamin D serum concentrations. Smoker group showed a higher posterior wall thickness (PW), left ventricular mass, and left ventricular mass index (LVMI). We identified positive correlations between LVMI and smoking history, PW and vitamin D serum, and body mass index and time of smoking history. Multiple linear regressions showed positive association of smoking history and LVMI and PW, also that serum vitamin D has a positive association with PW. PW was associated with smoking history and serum vitamin D, showing a deleterious effect on the heart of both variables. Conclusions: Smoking habit in adult women was associated with cardiac remodeling, and excess of vitamin D is associated with the action of smoking on cardiac variables. Thus, higher serum vitamin D values have a deleterious effect on the heart in this model.
Keywords: Myocardial dysfunction; Nutrition; Smoking; Vitamin D